Modeling the Relationship Between Customer Variables in Service Delivery and Their Impact on Customer Retention in Higher Education Institutions (Case Study at the Jimbaran Campus of ITB STIKOM Bali) - Jayanti, Ni Wayan Sri; Novita, Ni Kadek Tasya; Joyce, Joyce; Ayu Prayadni, Ni Luh Putu Dinsa; Indrawati, Ni Made (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to model the relationship between customer-related variables in service delivery and their impact on customer retention in higher education institutions, with a case study conducted at the Jimbaran Campus of the Institute of Technology and Business STIKOM Bali. The customer-related variables analyzed in this study include customer satisfaction, service quality, institutional image, and perceived value as independent variables, while customer retention is considered the dependent variable. Data were collected through a survey using questionnaires distributed to 100 active students enrolled in the Odd Semester of the 2024/2025 academic year at ITB STIKOM Bali Jimbaran Campus. The findings reveal a significant relationship between student satisfaction with the services provided and student retention. In addition, service quality, institutional image, and perceived value were also found to have a significant relationship with student retention. Simultaneously, all four independent variables were shown to significantly influence customer retention. The coefficient of determination test indicated that customer satisfaction, service quality, institutional image, and perceived value contributed 94.3% to customer retention, while the remaining 5.7% was attributed to other factors not examined in this study.